The Correlation Between Probiotics and Anxiety and Depression Levels in Cancer Patients: A Retrospective Cohort Study - Ye, Ziqi; Zhang, Yanfang; Du, Mengfei; Lu, Shaojia; Zhao, Qingwei; Yang, Si (Frontiers in Psychiatry, 2022)
Objective：Studies have shown a correlation between gut microbiota and the risk of anxiety and depression. However, these studies are mainly animal studies or clinical studies of non-cancer patients, there is still a lack of relevant studies in cancer patients. The main objective of this trial was to analyze the correlation between probiotics and the risk of anxiety and depression in cancer patients. Methods：We screened all cancer patients consecutively admitted to the inpatient department of our hospital in May 2020. A total of 290 cancer patients met our inclusion criteria. Then, we followed up all patients for 24 weeks. Patients with incomplete data, loss of follow-up, not taking probiotics consistently during follow-up, and who did not take specific probiotics were excluded. Ultimately, the number of patients enrolled was 82 in probiotics cohort and 100 in non-probiotics cohort. The 17-item Hamilton Depression Scale (HAMD-17) questionnaire was used to measure the depression levels of the patients, and we also used Hamilton Anxiety Scale (HAMA) questionnaire to assess the patients' anxiety levels. A logistic regression model was used to analyze whether the difference in baseline data of two cohorts would affect the final result. Results: Demographic and clinical characteristics of all cancer patients enrolled in probiotics cohort and non-probiotics cohort were similar except the cancer therapy (P=0.004). According to the HAMA score, we divided cancer patients into non-anxiety group (HAMA score <14) and anxiety group (HAMA score≥14). Similarly, cancer patients were also divided into non-depression group (HAMD-17 score ≤7) and depression group (HAMD-17 score >7). The results demonstrated that there was no statistical difference in the proportion of patients with anxiety (6.1% and 13.0%, respectively, P=0.121) and depression (30.5% and 23.0%, respectively, P=0.254) between probiotics and non-probiotics cohorts. The results of logistic regression model analysis further proved that the baseline difference in cancer therapy did not affect the conclusions. Conclusion: Our results still suggest that there is no significant correlation between probiotics and the risk of anxiety and depression in cancer patients. Therefore, we do not recommend supplementing probiotics for cancer patients to prevent anxiety and depression.